The impact of emergency department patient‐controlled analgesia (PCA) on the incidence of chronic pain following trauma and non‐traumatic abdominal pain1. (27th October 2018) - Rockett, M.; Creanor, S.; Squire, R.; Barton, A.; Benger, J.; Cocking, L.; Ewings, P.; Eyre, V.; Smith, J. E.
Summary: The effect of patient‐controlled analgesia during the emergency phase of care on the prevalence of persistent pain is unkown. We studied individuals with traumatic injuries or abdominal pain 6 months after hospital admission via the emergency department using an opportunistic observational study design. This was conducted using postal questionnaires that were sent to participants recruited to the multi‐centre pain solutions in the emergency setting study. Patients with prior chronic pain states or opioid use were not studied. Questionnaires included the EQ5D, the Brief Pain Inventory and the Hospital Anxiety and Depression scale. Overall, 141 out of 286 (49% 95%CI 44–56%) patients were included in this follow‐up study. Participants presenting with trauma were more likely to develop persistent pain than those presenting with abdominal pain, 45 out of 64 (70%) vs. 24 out of 77 (31%); 95%CI 24–54%, p < 0.001. There were no statistically significant associations between persistent pain and analgesic modality during hospital admission, age or sex. Across both abdominal pain and traumatic injury groups, participants with persistent pain had lower EQ5D mobility scores, worse overall health and higher anxiety and depression scores (p < 0.05). In the abdominal pain group, 13 out of 50 (26%) patients using patient‐controlled analgesia developed persistent pain vs. 11 out of 27 (41%) of those with usual treatment; 95%CI for difference (control – patient‐controlled analgesia) −8 to 39%, p = 0.183. Acute pain scores at the time of hospital admission were higher in participants who developed persistent pain; 95%CI 0.7–23.6, p = 0.039. For traumatic pain, 25 out of 35 (71%) patients given patient‐controlled analgesia developed persistent pain vs. 20 out of 29 (69%) patients with usual treatment; 95%CI −30 to 24%, p = 0.830. Persistent pain is common 6 months after hospital admission, particularly following trauma. The study findings suggest that it may be possible to reduce persistent pain (at least in patients with abdominal pain) by delivering better acute pain management. Further research is needed to confirm this hypothesis.